Answer:
Since it is a simultaneous equation,
Using elimination method, Multiply equation 1 by the co efficient of x in equation 2 and multiply equation 2 by the co efficient of x in equation 1.
Step-by-step explanation:
For further explanation , Please contact me through the comment section.
:)
Answer:
Mr.Lin's present age is 30 years now. His son is 8 years old now.
Step-by-step explanation:
Let L = Mr.Lin's present age,
S = his son's present age.
First equation is
L + S = 38. (1)
The second equation is
L + 3 = 3*(S+3) (2) ("In three years' time, Mr.Lin will be three times as old as his son.")
From (1), express S = 38-L and substitute it into (2). You will get
L + 3 = 3*((38-L)+3), or
L + 3 = 114 - 3L + 9,
4L = 114 + 9 - 3,
4L = 120,
L = 30.
Answer:
1.) f(x) = x*x - 7x + 10
2.) f(x) = x*x - 5x
3.) f(x) = 4*x*x - 5x - 6
4.) f(x) = 6*x*x -5x + 1
Step-by-step explanation:
1.) 2 and 5 (x -2)(x - 5) = f(x) = x*x - 7x + 10
2.) 0 and 5 f(x) = x*(x -5) = x*x - 5x
3.) -3/4 and 2 (x + 3/4)(x -2) = x*x - (5/4) x - 3/2,
need integers f(x) = 4xx - 5x - 6
4.) 1/2 and 1/3 (x - 1/2)(x - 1/3) = f(x)
x*x - 1/3 x - 1/2 x + 1/6
xx - 5/6 x + 1/6
6 xx - 5x + 1
Why now :cccccccccccccccccc
Answer:
3/8 is the probability
Step-by-step explanation: